Kazakhstan’s application of south Korea’s development model: possibilities and limitations (International relations and international law Journal, 2016)
In the the mid-1960s President Park Jung-hee actively began economic development of Korea. The main factor that speeds up the economic development of Korea was the effective leadership of the President Park’s Government, which succeeded to keep its stability after the civil war(The Korean war in 1950-1953). As well as a leader’s distinctive worldview, a strong economic and diplomatic policy, the struggle against the bureaucracy especially in the economic sector, timely implementation of the investment policy, the preparation of well-educated labor forces and the Korean culture of working diligently hard have contributed to the country’s economic growth. The strategy of economic development of the Park Jung Hee includes such areas as: 1) A strong government that allowed opposition activities 2) Pragmatic Approach 3) The active strategy to increase exports and the policy of openness 4) the Saemauel Movement (“New Village Movement”) There are many similarities and differences between Korea and Kazakhstan, but the model of Korea can be very useful for Kazakhstan, because they are similar, ﬁrstly, both adhere to the oriental culture (Korea’s Confucianism, Kazakhstan’s nomadic traditions and culture of Islam), they think the need of society is much more valuable than personal interests and secondly, they have a colonial past of the country, in terms of economic development, so the western policy, which was adopted in the early 90s couldn’t satisfy their expectations. Through these historical facts can be seen that the role of the country succumbed to the ﬂow of neo-liberalism does not look very attractive, thirdly, Kazakhstan and Korea are similar to each other in the struggle for competitiveness, they follow a policy based on maintaining a giant company. In Korea, it is “ Conglomerates (which is called in Korean “Chaebol”” in Kazakhstan “State-owned company”, in which the Government is directly involved.
Keywords: development model; Strategy of President Park Jung-hee; Strong government; Pragmatism; New Village Movement